Willingness to Vaccinate against Coronavirus Disease 2019 and Related Predictors among Non-Healthcare Personnel in Indonesia - Baroroh, Faridah; Suzalin, Ferawati; Indriani, Indriani; Sangadah, Siti; Istiningrum, Istiningrum; Wahyudi, Guntur Ilham; Rafdilla, Muhammad Rayhan Nadhil (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Herd immunity against COVID-19 can be realized when a minimum of 62% of the vulnerable population has been vaccinated. However, achieving uptake of recommended vaccination in the targeted population ultimately lies with the community’s willingness. Vaccine skepticism varies across demographic characteristics and stems from the perceived threats of being infected with COVID-19 while receiving the vaccine. AIM: This research was intended to determine the willingness to vaccinate against COVID-19 and its associated factors. METHODS: It employed a cross-sectional, then the collected data were analyzed using descriptive analytics: difference test and relationship analysis. Study with two online surveys on Google Forms and non-healthcare personnel as the research subjects. Screening with inclusion and exclusion criteria yielded 862 respondents spread over 32 provinces in Indonesia Results: showed no difference in COVID-19 knowledge scores in surveys 1 and 2 (76.0‒77.2; p=0.08). Age and education level are significantly related to COVID-19 knowledge scores (p<0.05). About 42.4% of respondents in survey 1 and 55.6% in survey 2 were willing to receive the vaccine, with 36.8‒45.3% feeling hesitant. The main reason for vaccine hesitancy (42.2%) and unwillingness (43.2%) was mistrust in the effects or benefits of the vaccine. Although demographic characteristics are not related to the willingness (p>0.05), the opposite is true for the COVID-19 knowledge level [OR:1.66; 95% CI:1.26–2.18]. Conclusion about half of the non-healthcare personnel (42.4‒55.6%) are willing to receive the vaccine, with knowledge of the disease being a predictor (p=0.00).